Features of the Circulation of ARVI Pathogens During of Emergence and Widespread of SARS-CoV-2 in the 2018–2021 - E. I. Burtseva; L. V. Kolobukhina; O. L. Voronina; A. V. Ignatjeva; E. A. Mukasheva; A. D. Panova; E. L. Feodoritova; K. G. Krasnoslodotsev; S. V. Trushakova; L. N. Merkulova; I. N. Khlopova; N. V. Breslav; et al. (Эпидемиология и вакцинопрофилактика)
Relevance. The long-term leadership of ARVI pathogens determines their significance in the damage caused to both health and the economy of the country. Aim. To identify the features of the structure of ARVI during the emergence and widespread spread of SARS-CoV-2. Materials and methods. The article uses methods used in epidemiological surveillance of acute respiratory viral infections. Results and discussion. The results of the diagnostic available ARVI pathogens monitoring during epidemic seasons 2018-2021 are presented. The tendency of greater engagement of aged group 15 y.o. and older in epidemic process by morbidity and hospitalization due to SARI was shown. 49 818 nasal swabs from patients with influenza infection, 36 044 – with ARVI and 59 062 – with SARS-CoV-2 were tested. The top three in the structure of ARVI were INF, HEV-D and HRSV (in the 2018–2019 season); INF, SARS-CoV-2 and HEV-D (2019–2020); SARS-CoV-2, HEV-D and HPIV/HCoV (2020–2021). The activity of viral pathogens also differed: for HPIV, HAdV, HEV-D, HMPV, a decrease in activity was noted during the appearance of SARS-CoV-2 (2019–2020) and some of its growth in the following season; in relation to HRSV and INF - a decrease in activity during the last two seasons, and for INF – extremely low activity in the 2020-2021 season; the activity of seasonal HCoV even increased slightly. The data of genetic analyses of SARS-CoV-2 positive samples showed the heterogeneity of its population with a representative of variants (Alfa, Delta) as well as endemic for Russia and Moscow variants only. The recommended composition of influenza virus vaccines for use in the 2021–2022 northern hemisphere influenza season and in the 2022 southern hemisphere influenza season are presented due to their drift changeability. Conclusions. SARS-CoV-2 was influenced by the activity of ARVI pathogens with the almost complete displacement of influenza viruses from the circulation in the period 2020–2021.